Multimedia telecommunications - Whyte, Bill (BT telecommunications series, 1997)
In this volume, written by engineers at the centre of the development of the industry, will be found a comprehensive survey of the wide range of applications encompassed by the term 'Multimedia Telecommunications'. From broadcast television to the specifics of data communications, from entertainment to decision-making, from the human interface to the details of the technology, all are essential facets of the subjects and are treated in this volume. For all users and providers of any form of multimedia service, researchers, development engineers, computer providers or users, IT and Information System managers, change managers in business or in the entertainment industry,Multimedia Telecommunications is essential reading.